Validity of Italian version of the Child Perceptions Questionnaire (CPQ(11-14)) - Olivieri, Armando (BioMed Central, 2013)
BACKGROUND: The Child Perceptions Questionnaire (CPQ(11-14)) is the most commonly used indicator of child oral health-related quality of life (OHRQoL), and its validity and reliability have been studied both in English and in other linguistic contexts. The aim of this study was to develop a CPQ(11-14) for use in Italy and to test its validity in a random sample of fourteen year-old Italian adolescents. METHODS: Once the CPQ(11-14)was translated into Italian and adapted for an Italian public, five hundred sixty-one adolescents were recruited for testing. Parents rated their social status; the children/adolescents were administered the questionnaire and underwent a dental examination during which their dental status was taken and recorded. Cronbach's alpha was used to assess the questionnaire’s internal consistency. Spearman's correlation coefficients were calculated to assess construct validity between the total and subscale scores and the respondents’ global ratings on oral health and well-being. Discriminant validity was analysed using the Kruskal-Wallis or Mann–Whitney tests in groups defined by gender, social position, caries experience and previous or no orthodontic treatment. RESULTS: The mean score on the CPQ(11-14) was 15.4 (SD=11.9), and the scores on all the domains were found to be highly skewed. Cronbach's alpha ranged from 0.85 to 0.90. The global ratings on oral health and well-being were correlated to the total score and to the sub-scores except for those regarding the functional limitations. There were significant differences in the two genders, in the groups that had already or had not yet undergone orthodontic treatment, and in the social classification groups, while the difference between those who had and those who did not have caries experience did not reach statistical significance. CONCLUSIONS: The Italian version of the CPQ(11-14) appears to be a reliable, valid instrument for Italian children/adolescents.